Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/jcm10143120
|View full text |Cite
|
Sign up to set email alerts
|

The Types and Proportions of Commensal Microbiota Have a Predictive Value in Coronary Heart Disease

Abstract: Previous clinical studies have suggested that commensal microbiota play an important role in atherosclerotic cardiovascular disease; however, a synthetic analysis of coronary heart disease (CHD) has yet to be performed. Therefore, we aimed to investigate the specific types of commensal microbiota associated with CHD by performing a systematic review of prospective observational studies that have assessed associations between commensal microbiota and CHD. Of the 544 published articles identified in the initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Our study was the first to use a large amount of clinical sample data. Such a large sample database can improve the accuracy of data analysis and model accuracy, and Chen et al [ 34 ] and Brown and Hazen [ 35 ] suggested that differences in gut microbiota can be used to predict cardiovascular disease. The ultimate goal is to optimize and develop the whole process from sampling device to extraction to library building and sequencing analysis and to achieve rapid, low-cost detection of intestinal flora in a large population [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our study was the first to use a large amount of clinical sample data. Such a large sample database can improve the accuracy of data analysis and model accuracy, and Chen et al [ 34 ] and Brown and Hazen [ 35 ] suggested that differences in gut microbiota can be used to predict cardiovascular disease. The ultimate goal is to optimize and develop the whole process from sampling device to extraction to library building and sequencing analysis and to achieve rapid, low-cost detection of intestinal flora in a large population [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that Bacteroides, Lactobacillus , and Rikenellaceae_RC9_gut_group were the groups with significant differential changes in the QS treatment of ACS. Chen 31 reported that Bacteroides were found in data from all 16 cohort studies (2210 patients) in the systematic evaluation assessing the association between commensal microflora and coronary artery disease. A clinical study published in Nature in 2020 found that 32 a high abundance of Bacteroides and a low abundance of Faecalibacterium were associated with inflammation and obesity, and that the administration of atorvastatin was negatively associated with dysbiosis of this flora.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal flora is associated with several scoring points of CHA 2 DS 2 -VAS C . Chen et al [36] studied the specific types of symbiotic flora associated with coronary heart disease (CHD) by systematically reviewing prospective observational studies to evaluate the relationship between symbiotic flora and CHD. Of the 544 published articles identified in the preliminary search, 16 articles from 16 cohort studies (2210 patients) were included in the analysis.…”
Section: Cha 2 Ds 2 -Vas C Score and Intestinal Floramentioning
confidence: 99%